Implikasi Hukum dan Etika Perbankan Syariah Terhadap Transaksi yang Terkait dengan Judi Online - Ady Riyansyah; Miswan Ansori (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
Islam encourages its followers to engage in muamalah activities, which must align with its basic principles, forming a crucial foundation for business conduct. Sharia banks, representing sharia-based financial businesses, have shown positive growth trends in Indonesia. This poses a challenge for the sharia banking industry, which must ensure compliance with sharia regulations. This research, a library study, involves collecting references from journal articles. Library research uses literature, including books, notes, and previous research reports. In Indonesia, online gambling is strictly prohibited by Law No. 7 of 1974 on Gambling Control. However, online gambling is becoming increasingly popular among Indonesians due to its convenience, with some sites facilitating payments through sharia bank accounts. To tackle this issue, sharia banking must enhance supervision and enforce strict regulations to prevent the misuse of services for online gambling. This study contributes significantly to understanding the legal and ethical implications of sharia banking concerning transactions related to online gambling. By highlighting the prohibition of gambling in Islam and its application in the digital age, this research provides a new perspective that integrates religious values with modern technological challenges.